PERAN PENYULUH PERTANIAN TERHADAP PENDAPATAN USAHATANI TOMAT DI DESA TONTONUNU KECAMATAN TONTONUNU KABUPATEN BOMBANA - Huswanto Huswanto; Musadar Mappasomba; Suriana Suriana (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2025)
The agricultural sector, particularly the cultivation of tomatoes in Tontonunu Village, exhibits considerable economic potential. However, the sector confronts impediments, including substandard yields, limited technological expertise, and reliance on intermediaries. Consequently, enhancing farmers' capabilities through agricultural extension initiatives is imperative to augment productivity and ensure their well-being. The objective of this study is to ascertain the impact of agricultural extension workers on the financial yield of tomato farming in Tontonunu Village, Tontonunu District, Bombana Regency. The research population comprised all 120 tomato farmers in Tontonunu Village. The sample size was determined using the Slovin formula with a standard error of 15%, resulting in a sample of 32 tomato farmers. The sampling method employed was simple random sampling. The data collection process involved the implementation of a survey method, which included the administration of a questionnaire and the conduction of interviews. The research variables encompassed the role of agricultural extension workers and tomato farm income. The data were processed using descriptive analysis. The results indicated that agricultural extension workers exhibited varied roles in carrying out their duties. Among the respondents who identified as facilitators, 43.75% were classified as being in the "very good" category, while 56.25% were in the "fairly good" category. The majority of respondents (96.875%) were classified as "fairly good," while a smaller proportion (3.125%) were designated as "very good." The role of educator elicited a range of outcomes, with all respondents (100%) falling within the fairly good category. Conversely, in the role of motivator, 71.875% of respondents were in the fairly good category, while 28.125% were in the very good category. The total income of the 32 farmers who participated in the study and who were engaged in tomato farming in Tontonunu Village was IDR 387,555,117. Furthermore, the income of each farmer exhibited significant variation, with the highest income reaching IDR 37,133,500 and the lowest income being IDR 2,214,750, with an average income of IDR 13,048,597 per season.